BARGAINING POWER PEREMPUAN PEKERJA RUMAHAN DENGANSKEMA PUTTING-OUT SYSTEM DALAM PEMENUHAN HAK SOSIALEKONOMI (STUDI DESKRIPTIF PADA PEREMPUAN PEKERJARUMAHAN PENGELEM ALAS KAKI, KELURAHAN PENJARINGAN) - Dewi, Intan Fatma; Nugroho, Fentiny (UI Scholars Hub, 2020)
The Putting-out system is a working system in the informal sector, most of the production process is felt outside of the plant or in a home and place that is self-selected by its employees and takes place without supervision at all from the employer. Through this scheme, the employer can streamline the cost of production by providing wages that are not comparable to working hours and the absence of protection for homeworkers. The women homeworkers must complete the target job with the working time exceeding twelve hours in a day even more. Consequently, their economic and social rights as workers are not met and neglected. The waiver of rights for a worker signifies the absence of protection from the Government for workers of the informal sector, especially women homeworkers. A distinction difference between formal and informal workers in the presence of bargaining power on workers. This study seeks to answer research questions: How do the bargaining power of women homeworkers in the wage given by employers? To answer this problem is used by the qualitative method. Data is collected through observations and in-depth interviews with women homeworkers who are in the status of housewife with husband then analyzed qualitatively. The results concluded that bargaining power owned by women homeworkers was very weak even nothing. They didn't even have the opportunity to negotiate with the wages they received. The interesting thing about this study is the analysis of how this condition can occur,